Truth and consequences: Bogus pipeline experiment in informal small business lending - Ulf Römer; Ron Weber; Oliver Mußhoff; Calcum G. Turvey (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2017)
The prevention of asymmetric information plays a major role in successful small business lending. The purpose of this research is to determine if small business applicants report their income information correctly when requesting a loan. Therefore, a randomized controlled trial bogus pipeline experiment was set up during a typical cash-flow analysis of a bank for small businesses in the Philippines. Results indicate that loan applicants of the treatment group reported a lower income, an effect which is most pronounced in the lowest income percentile. Moreover, our analyses reveal higher loan delinquencies in the control group.
Keywords: 330; Small business finance; Income reporting; Asymmetric information; Bogus pipeline; Randomized controlled trial